Chokeberry (Aronia melanocarpa) fruit extract modulates immune response in vivo and in vitro. (March 2020) - Gajic, Dragica; Saksida, Tamara; Koprivica, Ivan; Vujicic, Milica; Despotovic, Sanja; Savikin, Katarina; Jankovic, Teodora; Stojanovic, Ivana
Graphical abstract: Highlights: Chokeberry extract modulates gut-associated immune response in healthy C57BL/6 mice. It aggravates hyperglycemia during type 1 diabetes development in C57BL/6 mice. It stimulates dendritic cell and macrophage pro-inflammatory functions in vitro. Differentiation of T helper 1 cells is stimulated upon extract application in vitro. Abstract: Chokeberry ( Aronia melanocarpa ) is known for its anti-oxidant, anti-inflammatory and anti-diabetic properties. Since the effects of chokeberry extract on the immune response have been only sporadically assessed, our aim was to investigate chokeberry fruit water extract on the immune response in vivo and in vitro . When administered orally to healthy mice, the extract exerted immunomodulatory effects in the gut evidenced by the altered proportion of macrophages, dendritic cells and T cells. Importantly, oral consumption of the chokeberry extract resulted in blood glucose level increase in C57BL/6 mice with chemically-induced diabetes. These in vivo results were corroborated by observed up-regulation of nitric oxide and interelukin-1β production in macrophages and dendritic cells, up-regulated phagocytic activity of macrophages, increased T and B lymphocytes proportions and differentiation of interferon-γ-producing T cells in vitro . The obtained results imply that our chokeberry extract stimulates pro-inflammatory properties in immune cells of innate and adaptive immunity.